(untitled) (Deutscher Suchtkongress, 2023)
Following Caffeine, Nicotine and alcohol, cannabis is the most commonly used psychoactive substance globally, with more than 200 million estimated annual users, worldwide. Among lifetime cannabis users, between 8%-22% will develop Cannabis Use Disorder (CUD). In the European Union (E.U), treatment demand for CUD has increased in the past decade in almost all countries and CUD is currently the first most common reason for first-time drug-related treatment admission. In the first part of my talk, I will present a current mapping of Cannabis-Specific Treatment (CST) availability in Europe, based on data provided by national representatives ("Focal Points") of the European Monitoring Centre for Drugs and Drug Addiction (EMCDDA). Data regarding CST availability, type of treatment, national coverage and expected implementation of additional CST was available from 30 European countries. Results indicate that European countries devote considerable resources to treating CUD, via general substance use treatment tailored to the individual needs of the treatment seeking cannabis user or cannabis-specific interventions in addition to general substance use treatment. Emerging online CST programs are available in some European countries, allowing higher treatment availability and coverage. The second part of my presentation will review the current knowledge on predictors of effective treatment for CUD. I will focus on treatment moderators (i.e., patient-related characteristics which predict his/her odds to benefit from treatment) and mediators (i.e., treatment-related factors associated with the processes or mechanisms through which patients benefit from therapy) which were identified in empirically evaluated studies using defined, cannabis-related outcome measures.